Performance assessment of BeiDou-3 PPP-B2b real time pre-cise point positioning - Yu Lin; Laiyong Song; Jiaqi Shen; Zelin Mu (Scientific Reports)
Abstract To assess the performance of the PPP-B2b service, most existing studies typically store real-time PPP-B2b messages and leverage them to acquire precise satellite orbits and clock offsets. However, they often overlook potential interferences, such as occlusions and receiving delays, that may occur in real-time scenarios. Consequently, these studies fail to fully capture the real-time positioning capabilities of PPP-B2b. This study assesses real-time static and kinematic precise point positioning (PPP) solutions based on BDS-3 and BDS-3/GPS. The findings reveal that both BDS-3 and GPS systems demonstrate high signal matching with PPP-B2b, resulting in quicker convergence in real-time static PPP solutions and maintaining stable positioning accuracy without divergence. Particularly noteworthy is the higher precision observed in the north–south direction. Under BDS-3, the convergence time is approximately 26 min, with horizontal accuracy below 0.2 m, vertical accuracy below 0.4 m. Utilizing BDS-3/GPS reduces the convergence time by roughly 30% while maintaining comparable accuracy (horizontal accuracy below 0.2 m, vertical accuracy below 0.4 m). In real-time kinematic PPP solutions, based on the PPP-B2b algorithm, decimeter-level accuracy is attained, particularly in the north and south directions. The convergence time is approximately 1 h and 28 min, longer than real-time static PPP solutions, due to clock system biases. However, within the time periods after convergence and with no divergence, real-time kinematic PPP solutions achieve horizontal accuracy of 4 cm and vertical accuracy of 8 cm.